1993
DOI: 10.1002/j.1550-8528.1993.tb00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Treatment of Abdominally Obese Men

Abstract: Middle-aged men with abdominal obesity were treated in a double-blind study with moderate doses of transdermal preparations of testosterone (T), dihydrotestosterone (DHT), or placebo. This resulted in moderately elevated T concentrations and marked decreases in follicle stimulating and luteinizing hormones in the group treated with T, while the DHT group showed elevated DHT, markedly lower T values, and less diminution of gonadotropin concentrations. In the group treated with T visceral fat mass decreased (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
204
4
3

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(217 citation statements)
references
References 13 publications
6
204
4
3
Order By: Relevance
“…Correspondingly, a placebo-controlled, double-blinded study of aging men treated with HCG therapy to increase endogenous testosterone serum levels showed no increase in insulin sensitivity measured by the euglycemic hyperinsulinemic clamp despite an increase in LBM (Liu et al 2003). On the other hand, two placebo-controlled, double-blinded studies have reported an increase in insulin sensitivity during testosterone therapy assessed by the euglycemic hyperinsulinemic clamp in obese middle-aged men, in whom no predefined cutoff level for testosterone was used (Marin et al 1992;Marin et al 1993). In both studies, no significant increase in LBM was found.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, a placebo-controlled, double-blinded study of aging men treated with HCG therapy to increase endogenous testosterone serum levels showed no increase in insulin sensitivity measured by the euglycemic hyperinsulinemic clamp despite an increase in LBM (Liu et al 2003). On the other hand, two placebo-controlled, double-blinded studies have reported an increase in insulin sensitivity during testosterone therapy assessed by the euglycemic hyperinsulinemic clamp in obese middle-aged men, in whom no predefined cutoff level for testosterone was used (Marin et al 1992;Marin et al 1993). In both studies, no significant increase in LBM was found.…”
Section: Discussionmentioning
confidence: 99%
“…89 Young, lean subjects did not demonstrate any change in insulin sensitivity across a wide range of serum testosterone levels in a dose-response study, despite a dose-related reduction in FM. 90 Centrally obese middle-aged men receiving testosterone showed an improvement in insulin sensitivity (by hyperinsulinaemic/euglycaemic clamp studies) and a lowering of serum insulin levels; 52 however, these results were not seen with DHT 53 or oxandrolone (when administered to a similarly obese cohort). 55 In ageing men, hCG administered for 3 months did not affect insulin sensitivity (as measured by euglycaemic clamp).…”
Section: Relationship Of Endogenous Testosterone To Markers Of Cardiomentioning
confidence: 99%
“…Testosterone supplementation (oral for 8 months, transdermal for 9 months) of middle-aged men with mean BMI 29 kg/m 2 and abdominal obesity (and serum testosterone levels within the normal range) decreased visceral adiposity by 5-10% (0.4-0.6 kg), as assessed by CT, although total body fat (by total body potassium calculations) and subcutaneous adipose tissue mass (by CT) did not change. 52,53 These findings were not able to be replicated with dihydrotestosterone (DHT), 54 and a further study of similar duration using intramuscular testosterone could not reproduce these results despite selecting for obese subjects. 55 Regional DEXA examinations in one study of older men showing significant loss of FM with testosterone treatment suggested that this loss was significant only in the appendices and not within the trunk.…”
Section: Testosterone and Body Compositionmentioning
confidence: 99%
“…M&i n et al (18) report in this issue of OBESITY RESEARCH that treatment of men with abdominal obesity, using moderate doses of testosterone delivered by a transdermal patch, will decrease visceral fat mass and improve glucose disposal, dyslipidemia, and diastolic blood pressure.…”
Section: E Xavier Pi-sunyermentioning
confidence: 99%
“…
E Xavier Pi-SunyerM&i n et al (18) report in this issue of OBESITY RESEARCH that treatment of men with abdominal obesity, using moderate doses of testosterone delivered by a transdermal patch, will decrease visceral fat mass and improve glucose disposal, dyslipidemia, and diastolic blood pressure.Abdominal obesity is associated with increased risk of diabetes mellitus, hypertension, dyslipidemia. myocardial infarction, and stroke (23).
…”
mentioning
confidence: 99%